2014
DOI: 10.1002/jcc.23536
|View full text |Cite
|
Sign up to set email alerts
|

Explicit proton transfer in classical molecular dynamics simulations

Abstract: We present Hydrogen Dynamics (HYDYN), a method that allows explicit proton transfer in classical force field molecular dynamics simulations at thermodynamic equilibrium. HYDYN reproduces the characteristic properties of the excess proton in water, from the special pair dance, to the continuous fluctuation between the limiting Eigen and Zundel complexes, and the water reorientation beyond the first solvation layer. Advantages of HYDYN with respect to existing methods are computational efficiency, microscopic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 89 publications
0
38
0
Order By: Relevance
“…Although de-activation of fluorescence also requires protonation, it was shown by Van Thor and co-workers 5b that this occurs after the isomerization and at timescales beyond reach of our QM/MM simulations. We therefore will address the protonation process in the future, using either a classical approach for proton transfer, 14 a combination of empirical valence bond theory 15 and the QCFF/PI model, 16,17 or by means of QM/MM pKa calculations. 18 Inspection of the starting geometries revealed that rapid photoisomerization occurs only if the phenolate oxygen of the chromophore accepts at most one hydrogen bond from the environment, whereas no deactivation was observed if there are two or more hydrogen bonds.…”
Section: Hydrogen Bond Fluctuations Control Photochromism In a Reversmentioning
confidence: 99%
“…Although de-activation of fluorescence also requires protonation, it was shown by Van Thor and co-workers 5b that this occurs after the isomerization and at timescales beyond reach of our QM/MM simulations. We therefore will address the protonation process in the future, using either a classical approach for proton transfer, 14 a combination of empirical valence bond theory 15 and the QCFF/PI model, 16,17 or by means of QM/MM pKa calculations. 18 Inspection of the starting geometries revealed that rapid photoisomerization occurs only if the phenolate oxygen of the chromophore accepts at most one hydrogen bond from the environment, whereas no deactivation was observed if there are two or more hydrogen bonds.…”
Section: Hydrogen Bond Fluctuations Control Photochromism In a Reversmentioning
confidence: 99%
“…A number of classical nonpolarizable models for hydronium have been proposed 39,45,7779 . We tentatively chose the model proposed by Sagnella & Voth 77 with partial charges of −0.755 e on the O and +0.585 e on the H. The Lennard-Jones parameters were set equal to those of TIP3P water.…”
Section: Resultsmentioning
confidence: 99%
“…Applications have included GFP 40 , aquaporin 41 , acetic acid titration in water 42 , Fo-ATPase 43 and Nafion membranes 44 . Issues noted include the violation of detailed balance 45 , and an inability to study multiple protons due to integration instabilities 44 . A similar algorithm that also violates detailed balance uses a set of six geometric and energetic criteria to accept a hop and performs a local structure adjustment after each hop 46 .…”
Section: Introductionmentioning
confidence: 99%
“…246 A field by itself is the investigation of proton transfer in bulk water for which a myriad of FF-based techniques have been developed. [247][248][249][250][251][252][253] Finally, modern electronic structure methods may pave the way for ab initio MD simulations of large systems on extended time scales. They include hypertensor contractions 254 or density renormalization group techniques.…”
Section: Discussionmentioning
confidence: 99%